2014
DOI: 10.7717/peerj.558
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C in the wood frog,Rana sylvatica: reassessing the tissue-specific regulation of PKC isozymes during freezing

Abstract: The wood frog, Rana sylvatica, survives whole-body freezing and thawing each winter. The extensive adaptations required at the biochemical level are facilitated by alterations to signaling pathways, including the insulin/Akt and AMPK pathways. Past studies investigating changing tissue-specific patterns of the second messenger IP3 in adapted frogs have suggested important roles for protein kinase C (PKC) in response to stress. In addition to their dependence on second messengers, phosphorylation of three PKC s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
(102 reference statements)
1
7
0
Order By: Relevance
“…Another essential domain for frogs is the ‘Protein kinase domain’ that we found as the third more abundant (643 hits; 2.74%). This domain is supposed to play an important role in frogs in freezing tolerance during cold winters, likely inducing the transcription of antioxidant response genes ( Dieni & Storey, 2014 ). Although freezing winters are not common within the current range of O. cruralis , the relative abundance of protein kinase domains could have been important in the evolutionary history of Oreobates , a genus that may have originated at high altitude in the Andes ( Padial, Chaparro & De la Riva, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another essential domain for frogs is the ‘Protein kinase domain’ that we found as the third more abundant (643 hits; 2.74%). This domain is supposed to play an important role in frogs in freezing tolerance during cold winters, likely inducing the transcription of antioxidant response genes ( Dieni & Storey, 2014 ). Although freezing winters are not common within the current range of O. cruralis , the relative abundance of protein kinase domains could have been important in the evolutionary history of Oreobates , a genus that may have originated at high altitude in the Andes ( Padial, Chaparro & De la Riva, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another essential domain for frogs is 421 the 'Protein kinase domain' that we found as the third more abundant (643 hits; 2.74%). This 422 domain is supposed to play an important role in frogs in freezing tolerance during cold winters, 423 likely inducing the transcription of antioxidant response genes (Dieni & Storey 2014). Although 424 freezing winters are not common within the current range of O. cruralis, the relative abundance 425 of protein kinase domains could have been important in the evolutionary history of Oreobates, a 426 genus that may have originated at high altitude in the Andes (Padial et al 2008).…”
Section: Unigenes (N)mentioning
confidence: 99%
“…The PKC family of kinases is known to participate in many biological responses including the regulation of insulin sensitivity and lipid metabolism (Nishizuka 1995). Furthermore, it is has been shown to be strongly reduced in response to freezing in another frog species (Dieni and Storey 2014) In this thesis, in silico methods of predicting phosphorylation sites concluded that all enzymes isolated in this thesis were likely regulated by PKC in some capacity. Kinetic alterations were demonstrated after incubations that stimulated endogenous PKC that resulted in decreased substrate Km values for aldolase, CK and IDH.…”
Section: Future Directionsmentioning
confidence: 89%